“Restoration of the Past Scenery-Realm”: A Research on the Scenery-Realm Restoration of Jiang’s Fu Garden During Qing Dynasty in the Historical Revolution of the Humble Administrator’s Garden - Qian BIAN (Fengjing Yuanlin)
ObjectiveThe Humble Administrator’s Garden in Suzhou, initially constructed during the reign of Emperor Zhengde in Ming Dynasty, has undergone a series of transformations and periods of decline and revival. While academic discourse has established a foundational understanding of the garden’s historical evolution, further examination of its renovations and changes across different eras is still warranted. Concurrently, as the preservation of Chinese garden heritage garners increasing attention, researchers are increasingly focused on gaining indigenous insights from the restoration tradition of ancient Chinese gardens. It is therefore evident that the Humble Administrator’s Garden, which has retained its reputation and is still considered to partially maintain its original design intent and forms after hundreds of years, merits further research on its restoration events. The Jiang’s Fu Garden play a prominent role in the historical narratives of the Humble Administrator’s Garden during Qing Dynasty. Furthermore, the Fu Garden’s return to the original design intent of the Humble Administrator’s Garden and its role as a model for subsequent garden restorations endow it with exceptional significance in the context of the overall preservation of the scenery-realm of the Humble Administrator’s Garden. Consequently, an in-depth examination of the Fu Garden’s scenery-realm narratives in alignment with its restoration not only facilitates the approximation of the intricate truths of the historical evolution of the Humble Administrator’s Garden, but also enriches the historical understanding of the restoration tradition of ancient Chinese gardens. Previous research on the historical evolution of the Humble Administrator’s Garden also highlighted the significance of the Fu Garden’s “Jiu Guan Reng Fu” (restoration of the past scenery-realm). However, due to the limitations imposed by the differences in research subjects and the insufficiency of historical materials before, the key questions of what had been “fu” (restored) in this garden and what qualified the garden as a “fu” (restoration) of the past scenery-realm have not been sufficiently elucidated.MethodsThis research employs targeted searches within the Suzhou Library’s Ancient Book Database to augment the existing corpus of literature pertaining to Jiang’s Fu Garden. Concurrently, a typological approach is employed to classify and illustrate the elements of “j ǐ ng” (scenery), the experience of “jìng” (realm), and the temporal distribution of the written content present in the aforementioned literature. This is done with the objective of elucidating the clues and basic characteristics of the Fu Garden’s scenery-realm subsequent to its restoration. Subsequently, image materials either directly and indirectly related to the garden in question are collected and organized. By identifying and correlating the content of the images, the potential and limitations of schematic layout recovery of the Fu Garden are elucidated, and the distinctive significance of a core scenic area named Yuanxiang Hall within the garden for understanding the value orientation of the Fu Garden’s restoration is highlighted, as well as the feasible conditions for its research. Based on the above macroscopic understanding of textual and image materials, a further step is to conduct a close reading and analysis of key historical materials in order to answer the key questions.Results1) In response to the question of what had been restored, it can be said that there are two aspects to consider: The construction of scenery and the experience of realm. In terms of scenery construction, the research reveals the “Chi Shang Shan Lin” (hills and groves above the pool) as the core characteristic of the garden’s scenery, and the interaction between and transformation of various scenes within this core scenery provide the key basis for achieving the garden’s realm experience of “Shan Lin Zhi Xing” (nature of hills and groves) and “Xian Kuang Zhi Yu” (leisurely and spacious domain). Subsequently, the effects and sensory experience of other closely related elements of the core scenery constructed are summarized. These include the natural positioning and appropriate utility of the garden’s architectures, the continuous fragrance and seasonal scenery of flowers and trees, and the scene where animals, like birds and fish, return to their dwellings and are naturally drawn toward humans. In terms of realm experience, the research analyzes the generation of typical comprehensive experience and emotional activities in the garden from the perspectives of “Dong You Jian Jing Can” (roaming in motion and meditation in stillness) and “Ya Ji Yu Yuan Ju” (elegant gathering and garden dwelling), pointing out that the former, in short-term composite perceptions, is more likely to form differentiated results due to changes in mood, season, and combinations of dynamic and static appreciation, while the latter, through long-term interactive attachment and more nuanced examinations over time, can make the emotional sustenance of guests in the garden more genuine and varied. 2) In response to the question of what qualified the garden as a restoration of the past scenery-realm, the focus is on the “Yuanxiang Hall” area as a clue to explore the value orientation of the Fu Garden’s restoration. In particular, the starting point is the schematic layout recovery of this area. Then, a comparison of the design intent and scenery-realm between this area and its predecessor named “Ruoshu Hall” in the Wang’s Humble Administrator’s Garden, reveals that the character “fu” (restoration) in the name of the Fu Garden not only refers to the actual restoration of the scenery-realm, but also emphasizes the continuation of the deeper intentions of the garden design.ConclusionThe research reviews the research process, rethinks the methods of extracting features of the scenery-realm of historical gardens, and considers the approaches to understanding the restoration tradition of ancient Chinese gardens.